Strategy to Improve Higher Education Quality through OBE and Benchmarking: Strategi Meningkatkan Kualitas Pendidikan Perguruan Tinggi dengan OBE dan Benchmarking - Mohamad Agus Salim; Arthur Simanjuntak; Nova Syahrani Arasid; Indri Mariska Putri; Suhada Suhada; Dwi Cahyono (ADI Pengabdian Kepada Masyarakat, 2025)
Growing demands for global competitiveness and accountability push universities to adopt innovative strategies. In the context of higher education in Indonesia, there is a growing recognition of the need to align with international standards to improve quality, relevance, and competitiveness. One promising approach is the adoption of Outcome-Based Education (OBE), which emphasizes clear learning outcomes and continuous improvement, supported by systematic quality assurance. This study examines how OBE, when combined with international benchmarking, can effectively enhance educational quality and institutional performance. The aim is to explore the role of benchmarking in identifying performance gaps and adopting best practices to support sustainable academic improvement. A qualitative research design was employed, utilizing data collected from document analysis, semi-structured interviews, and institutional case studies. These sources provided a comprehensive understanding of the strategies implemented and the institutional changes observed. The findings reveal that integrating OBE with international benchmarking significantly improves curriculum alignment, student centered learning, and internal quality assurance systems. Benchmarking serves as a strategic tool to compare institutional practices with global standards, fostering the adoption of innovative pedagogical and assessment methods. It also contributes to improving academic reputation and international rankings. The integration of OBE and benchmarking provides a practical and sustainable framework for higher education institutions to enhance academic quality and global competitiveness. This model supports continuous institutional improvement and positions Indonesian universities to better meet global challenges in the education sector.